Metastatic cholangiocarcinoma mimicking tuberculosis in a cow. (November 2021) - Elbert, Jessica A.; Sanchez, Susan; Rissi, Daniel R.
Here we describe a metastatic hepatic cholangiocarcinoma (cholangiocellular carcinoma) in a 14-y-old Beefmaster cow that was euthanized because of depression and progressive weight loss. Gross changes included coalescing, white-to-yellow, firm-to-hard nodules with central areas of necrosis and mineralization that effaced much of the hepatic parenchyma, omentum, mesentery, ruminal serosa, and diaphragm. A fresh sample of a hepatic nodule was submitted for a modified acid-fast (MAF) stain during autopsy to rule out tuberculosis. The MAF stain was inconclusive, and the sample was subsequently submitted for a PCR assay for Mycobacterium spp. Histologically, all nodules consisted of a neoplastic proliferation of epithelial cells surrounded by extensive areas of desmoplasia, consistent with a metastatic cholangiocarcinoma. PCR for Mycobacterium spp. was negative. Although the histologic diagnosis in our case was metastatic hepatic cholangiocarcinoma, gross changes were strikingly similar to those described in cases of tuberculosis, highlighting the need to remain vigilant in the identification of zoonotic and suspected foreign animal diseases during autopsy to protect human health.